2008
DOI: 10.1177/153567600801300405
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Risk Assessment of a Novel Antifungal Defensin Peptide from Chickpea (Cicer arietinum L.)

Abstract: Risk assessment of an antifungal peptide is a prerequisite before using the corresponding gene to produce broad-spectrum, fungal-resistant GM crops

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Growth inhibition by plant defensins of a wide range of pathogenic fungi is not associated with toxicity in mammalian or plant cells (Thomma et al, 2002). Studies of the biological activity, stability, and range of toxicity of an isolated chickpea defensin (Ca-AFP) revealed that there are no risks in using the gene in the production of transgenic crops (Islam, 2008). However, to date, three defensin-related proteins have been described as allergens (Singh et al, 2006;Petersen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Growth inhibition by plant defensins of a wide range of pathogenic fungi is not associated with toxicity in mammalian or plant cells (Thomma et al, 2002). Studies of the biological activity, stability, and range of toxicity of an isolated chickpea defensin (Ca-AFP) revealed that there are no risks in using the gene in the production of transgenic crops (Islam, 2008). However, to date, three defensin-related proteins have been described as allergens (Singh et al, 2006;Petersen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…3 Fungicide application is the most widely practiced method to control yield loss due to fungal attack. 4 Development of resistance in pathogens against conventional antifungal agents as well as growing concerns regarding the hazardous impact of fungicide on the environment necessitates the development of novel methods to control fungal pathogens. Genetic engineering has proved to be providing a good solution to this issue by transgenic expression of antifungal genes that confer resistance to fungal pathogens and enhance crop yield.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Plants are exposed to various biotic and abiotic stress factors such as drought and temperature, as well as attack by various pathogens and pests, which results in huge loss of crop yield worldwide amounting to 30–50 billion USD annually. , Fungal pathogens causes 70% of the major crop diseases . Fungicide application is the most widely practiced method to control yield loss due to fungal attack . Development of resistance in pathogens against conventional antifungal agents as well as growing concerns regarding the hazardous impact of fungicide on the environment necessitates the development of novel methods to control fungal pathogens.…”
Section: Introductionmentioning
confidence: 99%